Persepsi Organisasional Politik: Tinjauan Sistematis dan Arah Penelitian Masa Depan - Basoeki, Tommy Oktavian (Universitas Airlangga, 2024)
This article aims to systematically review research on Perceptions of Organizational Politics (POP) by addressing gaps in the literature through discussions on scientific contributions and key issues from previous findings related to the dimensions, antecedents, and consequences of POP. This study analyzes 17 publications found in the Scopus database, published between 2016 and 2023. The findings reveal that POP is a complex concept with diverse definitions and dimensions, influenced by various organizational and individual factors that significantly affect organizational outcomes. This review highlights that, although limited to publications from a single database, the article provides valuable recommendations for future research to explore POP more broadly using other databases. It also offers a critical systematization of the limited but significant POP literature, providing valuable insights for academics and practitioners to deepen their understanding of this concept. Furthermore, the article opens opportunities for further research to address the limitations of empirical testing related to POP, including its antecedents, consequences, theories, and methodologies. Thus, this article not only enriches the POP literature but also provides direction for future research and practical development. Keywords: Perceptions of Organizational Politics, Systematic Literature Review